THE INFLUENCE OF CALLA AND MOTIVATION TOWARD WRITING ABILITY OF THE FIRST SEMESTER ACCOUNTING STUDENTS AT POLITEKNIK SEKAYU - Alfha Desiana Maria (Didascein : Journal of English Education, 2021)
Cognitive Academic Language Learning Approach (CALLA) model was used in defining about assumptions, beliefs, and theories about the nature of language and language learning. This study applied experimental research with factorial design. The population of this study was all the students of Accounting program in Politeknik Sekayu. 80 students of Accounting program participated in this study, taken by by using two stage random sampling. Test and a ready-made questionnaire of motivation were applied to obtain the data. The analysis was used t-test and two way ANOVA. Based on the finding of the result score of the motivation questionnaire in experimental group showed that 50% students had high motivation and 50 % students had low motivation. The distribution of CALLA scores were normal, since significant value was higher than 0.05. The data of CALLA and conventional model were homogenous since the result of homogeneity of variance testing indicated that significant value of all the data were higher than the significant of p-value 0.05.The result of analysis test of two ways ANOVA showed that there was a significant interaction effect of CALLA and motivation toward the First Semester of Accounting Program Students’ Hortatory Exposition writing ability at Politeknik Sekayu, since the significant value was 0.006 lower than 0.05. Keywords:CALLA model, motivation, writing ability